Thesaurus of international trade terms - International Trade Centre UNCTAD; International Trade Centre UNCTAD/GATT. (Geneva : International Trade Centre UNCTAD/GATT, 1985)
This book is intended to be used with both manual and computerized systems of information storage, retrieval and dissemination
In English, with French and Spanish equivalents.
Includes bibliographical references.
ijb, 17/01/2019
Loans
Keywords: Subject headings; Subject headings; Subject headings